2016
DOI: 10.1111/jipb.12472
|View full text |Cite
|
Sign up to set email alerts
|

An exon skipping in a SEPALLATA‐Like gene is associated with perturbed floral and fruits development in cucumber

Abstract: S (2016) An exon skipping in a SEPALLATA-Like gene is associated with perturbed floral and fruits development in cucumber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Cucumber (Cucumis sativus L.) is a major vegetable crop cultivated worldwide, and is also a model system for flower development studies owing to its diversity of floral sex types [38][39][40]. Our previous study had identified 43 MADS-box family genes in cucumber, and some of them may function in determining the flower organ identity and floral transition [1].…”
Section: Introductionmentioning
confidence: 99%
“…Cucumber (Cucumis sativus L.) is a major vegetable crop cultivated worldwide, and is also a model system for flower development studies owing to its diversity of floral sex types [38][39][40]. Our previous study had identified 43 MADS-box family genes in cucumber, and some of them may function in determining the flower organ identity and floral transition [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study revealed the expression pattern of 43 MADS-box genes in cucumber (Hu and Liu, 2012). CUM1, CUM10, CUM26, CsAP3, and CsSEP2 are currently known cucumber MADS-box genes that play essential roles in flower and fruit development (Kater et al, 1998;Kater et al, 2001;Sun et al, 2016;Wang et al, 2016), whereas there are still a considerable portion of MADS-box genes need to be functionally characterized. In this study, we identified the CsSHP gene in cucumber and revealed the roles in fruit maturation and floral organ determination.…”
Section: Discussionmentioning
confidence: 99%
“…Cucumber is one of the economically-important vegetable crops cultivated worldwide, and ABCDE model genes may play very important roles in flower development. However, only a number of floral homeotic genes from cucumber have been investigated in detail [28,31,37,38]. In this study, an AG homologous gene, CsMADS24, was isolated from cucumber developing flowers.…”
Section: Discussionmentioning
confidence: 99%